THE RELATIONSHIP BETWEEN BREASTFEEDING TECHNIQUES AND THE INCIDENT OF SCRATCHED NIPPLES IN PUBLIC WOMEN AT TPMB ARI KRISTIYANI, TAMBUN SELATAN DISTRICT, BEKASI - Maygrani, Finda; Widaningsih, Ida (NHM PRESS, 2024)
According to the results of the Indonesian Toddler Nutritional Status Study (2020), as many as 27.67% of toddlers in Indonesia experience stunting. One intervention that is considered capable of overcoming the problem of stunting is optimal exclusive breastfeeding. Indonesia's exclusive breastfeeding coverage in 2022 was recorded at only 67.96%, down from 69.7% in 2021. The causes of failure to provide exclusive breastfeeding are three factors, namely psychosocial factors, socio-demographic factors and health service factors. Providing knowledge about early breastfeeding will increase positive attitudes and the success of exclusive breastfeeding. The aim of this research is to identify the relationship between breastfeeding techniques and the incidence of sore nipples in postpartum mothers at TPMB Ari Kristiyani, Tambun Selatan District, Bekasi Regency in 2023. The research method used is a cross sectional survey method. sampling using a total sampling technique of 30 respondents. Univariate analysis uses a frequency distribution and for bivariate tests uses the Chi Square test. This research uses primary data from filling out questionnaires by respondents. The results showed that of The P value has a value of 0.000 < 0.05, which means that Ha is accepted and Ho is rejected or means that there is a relationship between breastfeeding technique and the incidence of sore nipples at TPMB Ari Kristiyani. It is hoped that this research will become a reference for educational materials in independent practice settings, especially breast-feeding techniques so that the breastfeeding process is comfortable and pain-free. It is also hoped that this research will become a basis and reference for further research related to increasing knowledge and become material for further study